2010
DOI: 10.1136/emj.2009.086967
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature of trauma patients on admission to hospital: a comparison of anaesthetised and non-anaesthetised patients

Abstract: This study confirmed that patients anaesthetised in the prehospital phase of care had a significantly lower admission body temperature. This has led to a change in the author's prehospital practice. Anaesthetised patients are now actively surface heated and have whole body insulation to prevent further heat loss in an attempt to conserve body temperature and improve outcome. This is an example of best in-hospital anaesthetic practice being carried out in the prehospital phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…However, our study aimed to evaluate intrinsic properties of studied devices, and describe their capacity to prevent heat loss and the torso model ensured equal test conditions for each product. Patients with major trauma often require prehospital anaesthesia; in this group of patients physiological responses to heat loss are often diminished due to the severity of injuries and response to anaesthetic drugs so the torso model may apply more closely to anaesthetised than spontaneously ventilating patients 7 15. Further research using randomised clinical trials comparing studied devices on patients with major trauma is required to identify the best heat preservation strategy but informed consent would be challenging and such studies expensive to perform.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study aimed to evaluate intrinsic properties of studied devices, and describe their capacity to prevent heat loss and the torso model ensured equal test conditions for each product. Patients with major trauma often require prehospital anaesthesia; in this group of patients physiological responses to heat loss are often diminished due to the severity of injuries and response to anaesthetic drugs so the torso model may apply more closely to anaesthetised than spontaneously ventilating patients 7 15. Further research using randomised clinical trials comparing studied devices on patients with major trauma is required to identify the best heat preservation strategy but informed consent would be challenging and such studies expensive to perform.…”
Section: Discussionmentioning
confidence: 99%
“…This often involves temporary paralysis during rapid sequence induction procedures that predispose the patient to increased risk of body heat loss. Importantly, Langhelle et al and Lapostolle et al reported that patients who had been intubated before arriving at the hospital emergency department consistently had lower core body temperatures than those who had not been intubated (13,16). According to Andrzejowski et al, the administration of anaesthesia (including agents used for sedation and paralysis) for intubation can reduce the patient's core body temperature by 1.6°C via thermal redistribution (17).…”
Section: Discussionmentioning
confidence: 99%
“…The main benefits of active re-warming are in these cases to reduce energy consumption and increase comfort [15,16]. In patients with impaired shivering response due to severe hypothermia, injury, disease, intubation or use of drugs, insulation alone may not be sufficient to maintain core temperature and these patients may require active warming [17,18]. …”
Section: Discussionmentioning
confidence: 99%